Analysis of Factors Influencing Rice Production in Labuhan Batu District - Tri Shinta Elvina; Akbar Siregar; Rahmanta Ginting (Journal of Social Research, 2023)
This research aims to analyze the factors that influence rice production in Labuhan Batu Regency. The research was conducted in Labuhanbatu Regency, North Sumatra Province. The determination of the research area was carried out purposively with the consideration that the Labuhanbatu Regency area according to BPS data in 2021 experienced a deficit in milled dry unhulled rice production and corn production in Labuhanbatu which was not commensurate with the population growth. The population in this study was all existing sub-districts. in Labuhanbatu Regency there are 9 sub-districts and the method used in sampling is a census and sample selection is taken from 9 sub-districts in Labuhan Batu District. Data analysis in this research uses Multiple Linear Regression Analysis (multiple regression) through the Cobb-Douglas function. The results of this research are that in the research the variable Land Area influences rice production because t count > t table (6,184 > 2,010) and the level is significant 0.000 < 0.05. In the research, the Labor variable influences rice production because t count > t table (3.001> 2.010) and the significance level is 0.002 < 0.05. In research, the fertilizer variable influences rice production because t count > t table (5.075 < 2.010) and the significance level is 0.000 < 0.05. In the research, the Seed variable influences rice production because t count > t table (4.341 < 2.010) and the significance level is 0.000 < 0.05. Form a linear regression model from the Cobb-Douglas production function to study the factors that influence rice production. Showing the results of (bx1+bx2+bx3+bx4) = 4,761, meaning that in this study the land area, labor contribution, fertilizer use, and seed use can be projected to see the amount of rice production in Labuhan Batu of 47.61%.